Falcaria vulgaris extract attenuates diabetes–induced kidney injury in rats - Jalili Cyrus; Roshankhah Shiva; Salahshoor Mohammad Reza (Asian Pacific Journal of Tropical Biomedicine, 2019)
Objective: To assess the effects of Falcaria vulgaris (F. vulgaris) as an antioxidant on damage to kidney of diabetic rats. Methods: Diabetic rats were established via streptozotocin (60 mg/kg). Various doses of F. vulgaris extracts (50, 100 and 150 mg/kg) and streptozotocin + F. vulgaris extracts were administered via intraperitoneal (i.p) injection to 48 rats (n=8 per group) for 28 d. Subsequently, ferric ion reducing antioxidant power (FRAP) of renal tissue, thiobarbituric acid reactive species, blood glucose concentrations, insulin, nitrite oxide, the weight of animals, glomeruli characteristics and kidney function were evaluated. Results: Compared with the control rats, diabetic rats showed significant increase in malondialdehyde, blood urea nitrogen, creatinine, blood glucose, nitrite oxide contents in renal tissues, and glomerular diameter. Furthermore, tissue FRAP level, body weight, number of glomeruli and plasma insulin were markedly reduced in diabetic rats when compared with the control group (P < 0.05). However, in all F. vulgaris and F. vulgaris + streptozotocin groups, malondialdehyde level, blood urea nitrogen, creatinine, glomerular diameter, nitrite oxide, and glucose levels were decreased significantly; meanwhile, tissue FRAP level, body weight, glomeruli number and insulin serum level were increased, compared to the control diabetic group (P < 0.05). Conclusions: F. vulgaris extract alleviates renal damage in diabetic rats.